Characterization of four novel bacteriophages targeting multi-drug resistant Klebsiella pneumoniae strains of sequence type 147 and 307 - Ponsecchi, Greta; Olimpieri, Tommaso; Poerio, Noemi; Antonelli, Alberto; Coppi, Marco; Di Lallo, Gustavo; Gentile, Mariangela; Paccagnini, Eugenio; Lupetti, Pietro; Lubello, Claudio; Rossolini, Gian Maria; Fraziano, Maurizio; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
The global dissemination of multi-drug resistant (MDR) pathogenic bacteria requires the rapid research and development of alternative therapies that can support or replace conventional antibiotics. Among MDR pathogens, carbapenem-resistant Klebsiella pneumoniae (CR-Kp) are of particular concern due to their extensive resistance profiles, global dissemination in hospital environments, and their major role in some life-threatening infections. Phages, or some of their components, are recognized as one of the potential alternatives that might be helpful to treat bacterial infections. In this study, we have isolated and characterized four lytic bacteriophages targeting K. pneumoniae strains of Sequence Type (ST) 307 or ST147, two predominant high-risk clones of CR-Kp. Phages, designated vB_KpS_GP-1, vB_KpP_GP-2, vB_KpP_GP-4, and vB_KpP_GP-5, were isolated from sewage wastewater samples. The vB_KpS_GP-1 phage was a siphovirus unable to establish lysogeny with its host, while the other three were podoviruses. While 85.7% of K. pneumoniae strains of ST307 were selectively lysed by the phages vB_KpS_GP-1 or vB_KpP_GP-5, the other two phages were able to lyse all the tested strains of ST147 (n = 12). Phages were stable over a broad pH and temperature range and were characterized by burst sizes of 10–100 plaque forming units and latency periods of 10–50 minutes. Genome sequencing confirmed the absence of antibiotic resistance genes, virulence factors or toxins and revealed that two phages were likely members of new genera. Given their strictly lytic nature and high selectivity towards two of the major high-risk clones of K. pneumoniae, cocktails of these phages could represent promising candidates for further evaluation in in vivo experimental models of K. pneumoniae infection.